Aplikasi Group Touring Dengan Metode Location Based Service Berbasis Mobile - Abri Yanto, Hari (Jurnal Teknik Indonesia, 2023)
Purpose:  to create an application that can help riders who are about to do touring to be safer and more comfortable by knowing the position of each other rider member. Methods: The research method used is to analyze the problem, design the system, implement and test the system by using the location-based service method and utilizing GPS services to get a position and calculate the distance between riders to determine warning notifications if a driver is left behind and take advantage of realtime database using firebase. The type of research being carried out is experimental research by testing the application that will be made by making several test scenarios. Results: The results of application testing using black box testing show the application can track the location of the rider, calculate the distance between the riders, determine the head of the group and provide warning notifications if a rider is left behind. Conclusion: It can be concluded that overall this touring group application can carry out the function of tracking riders according to what is expected and creating an Android-based touring group application that can help touring riders